3G wireless networks - Smith, Clint
Pin down the technical details that make 3G wireless networking actually work. In 3G Wireless Networks, experts Clint Smith and Daniel Collins dissect critical issues of compatibility, internetworking, and voice/data convergence, providing you with in-depth explanations of how key standards and protocols intersect and interconnect